Potential management interventions to mitigate greenhouse gas emissions from tea cultivation. Issue 6 (1st November 2020) - Rigarlsford, Giles; de Silva, Jacquie; Tuwei, Gabriel; Redfern, Sally; Kulak, Michal; Miah, Jamal H.; Sim, Sarah
Abstract: Previous studies have confirmed the agricultural stage as an important contributor to total tea life cycle greenhouse gas (GHG) emissions. We therefore focus on the growing and processing of black tea and evaluate the GHG reduction potential of possible agricultural management interventions for tea produced from Unilever's tea estates and factories in Kenya. A baseline GHG footprint was calculated using data collected over four years. Potential interventions to reduce the GHG footprint per kg of black tea focused on key drivers (yield and fertiliser use) of the GHG footprint. These interventions and their effects on production are evidence-based but hypothetical and relate to possible changes in: (1) Harvesting practices; (2) Fertiliser application (timing) and (3) Organic production. Improvements in fertiliser application and harvesting practices could potentially deliver 16% and 9% reduction in GHG emissions, respectively. Under favourable conditions (sourcing fertiliser locally and no yield decline), changing to organic production could theoretically deliver 25% reduction in GHG emissions. However, under less favourable conditions (European sourced fertiliser and 30% yield decline), GHG emissions could increase by 41%. The availability of locally sourced organic fertiliser, sufficient to maintain nitrogen application rates, is seen as the biggest challenge in delivering sustainable organic tea cultivation.